2020
DOI: 10.1186/s12610-020-00111-7
|View full text |Cite
|
Sign up to set email alerts
|

Excessive unilateral proliferation of spermatogonia in a patient with non-obstructive azoospermia – adverse effect of clomiphene citrate pre-treatment?

Abstract: Background: Clomiphene citrate has been proposed as pre-treatment for infertile men with non-obstructive, testicular azoospermia (NOA) before surgery for testicular sperm extraction (TESE), especially when serum testosterone is low. Case presentation: Here, we report on a 33-year old azoospermic patient with a previous history of repeated "fresh" TESE and clomiphene citrate therapy (50 mg/day over 6 months) before undergoing microscopically assisted, bilateral testicular biopsy. Comprehensive histological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 49 publications
(65 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, the increased number of spermatogonia (proliferation of spermatogenesis) observed in testis of the alcohol and cART treated groups, could be an attempt to increase the germ cell pool so as to counteract the diminishing spermatogenesis processes which is in line with a previous clinical study that reported a massive increase in the number of normally differentiated spermatogonia and elevated spermatogonia proliferative activity in a biopsy of patient with non-obstructive azoospermia [43]. Additionally, the (LAF and diameter (LD) were both slightly increased in the A group but significantly increased in the A+cART group, suggesting varying degrees of germ cell layer reduction due to different treatments as well as seminiferous tubule shrinkage.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the increased number of spermatogonia (proliferation of spermatogenesis) observed in testis of the alcohol and cART treated groups, could be an attempt to increase the germ cell pool so as to counteract the diminishing spermatogenesis processes which is in line with a previous clinical study that reported a massive increase in the number of normally differentiated spermatogonia and elevated spermatogonia proliferative activity in a biopsy of patient with non-obstructive azoospermia [43]. Additionally, the (LAF and diameter (LD) were both slightly increased in the A group but significantly increased in the A+cART group, suggesting varying degrees of germ cell layer reduction due to different treatments as well as seminiferous tubule shrinkage.…”
Section: Discussionsupporting
confidence: 82%
“…PCNA is also a useful marker for diagnosing germinal arrest, which is the result of deterioration in DNA synthesis [ 77 ]. In one study, clomiphene citrate was used to treat infertile men with NOA; subsequent testicular sperm extraction showed that most tubules (>70%) exhibited no tubular lumen or regular seminiferous epithelium, but there were a large number of spermatogonia-like cells that exhibited normally differentiated spermatogonia with enhanced proliferation activity (positive for PCNA) [ 78 ]. The mechanism for effective spermatogenesis involves germ cell type-specific posttranslational modifications of histones, and histone variants play an important role.…”
Section: Research On Pcna In Andrologymentioning
confidence: 99%